Difficulties of Management of Multiple Synchronous Bone Tumors in Li-Fraumeni Syndrome - Marine Huby; Laurence Brugières; Eric Mascard; Nathalie Gaspar; Stéphanie Pannier; Jean-Charles Aurégan (Case Reports in Orthopedics)
Li-Fraumeni syndrome is a rare inherited disease characterized by the early onset of multiple primary malignant tumors. Sarcomas account for more than 30% of all malignant tumors occurring at pediatric age. Furthermore, it was shown that the rates of second cancer were higher in childhood cancer survivors. We report the case of a patient with Li-Fraumeni syndrome who was referred to us with three synchronous skeletal tumors. This unique situation led to difficulties for the medical team regarding the diagnosis of malignancy and the surgical treatment to propose. The discovery of multiple lesions in the extension assessment underlines the usefulness of whole-body imaging for the follow-up of patients with germline TP53 mutations. Most recent guidelines now recommend annual whole-body MRI for screening for cancer patients carrying germline TP53. With this report, we aim to share our experience with this rare situation in order to improve care about these specific cases.